Casca de banana em dietas para coelhos em crescimento - Falcone, Diuly Bortoluzzi (2019)
This study aimed to evaluate the use of banana peel (BP) as an energetic ingredient in diets for growing rabbits. The biological assay was conducted in a completely randomized design in the Cuniculture Laboratory of the Department of Animal Science of the Federal University of Santa Maria. A total of 45 New Zealand White rabbits (9 animals / treatment), weaned at 35 days of age were feed with different levels of BP as a replacement maize: 0BP (control diet without BP), 25BP (BP as a replacement 25% of maize), 50BP (BP as a replacement 50% of maize), 75BP (BP as a replacement 75% of maize) and 100BP (BP as a replacement 100% of maize). The results were submitted to analysis of variance and the means of the evaluated parameters were compared by the Tukey test at 5% of significance. The intake, daily weight gain, feed conversion and carcass yield were not altered by the increasing substitution of maize by BP. The water, protein and ash contents, as well as the color meat (L *, a * and b *), also did not present significant differences between the treatments. Likewise, the characteristic of the coat remained identical, regardless of the levels of BP used in the diet. Maize replacement by BP reduced linearly the feed cost, with the 0BP diet most costly (R$ 1.11 / kg) and 100BP (R$ 1.02 / kg) the most economical. The results obtained in this study showed that the BP can completely replace the maize in the diets for growing rabbits, at a lower cost and keep similar performance, meat quality and great pelage.